Metal hydride hydrogen storage tank for fuel cell utility vehicles. (13th March 2020) - Lototskyy, Mykhaylo; Tolj, Ivan; Klochko, Yevgeniy; Davids, Moegamat Wafeeq; Swanepoel, Dana; Linkov, Vladimir
Abstract: The "low-temperature" intermetallic hydrides with hydrogen storage capacities below 2 wt% can provide compact H2 storage simultaneously serving as a ballast. Thus, their low weight capacity, which is usually considered as a major disadvantage to their use in vehicular H2 storage applications, is an advantage for the heavy duty utility vehicles. Here, we present new engineering solutions of a MH hydrogen storage tank for fuel cell utility vehicles which combines compactness, adjustable high weight, as well as good dynamics of hydrogen charge/discharge. The tank is an assembly of several MH cassettes each comprising several MH containers made of stainless steel tube with embedded (pressed-in) perforated copper fins and filled with a powder of a composite MH material which contains AB2 - and AB5 -type hydride forming alloys and expanded natural graphite. The assembly of the MH containers staggered together with heating/cooling tubes in the cassette is encased in molten lead followed by the solidification of the latter. The tank can provide >2 h long H2 supply to the fuel cell stack operated at 11 kWe (H2 flow rate of 120 NL/min). The refuelling time of the MH tank ( T = 15–20 °C, P (H2 ) = 100–150 bar) is about 15–20 min. Highlights: Necessity to increase weight of FC power modules for utility vehicles including forklifts. Low temperature intermetallic hydrides combine compact H2 storage with high weight. Further weight increase was achieved by encasing the MH containers in molten lead. MH tank comprising of eight lead-encased MH cassettes was integrated in forklift FC power module. The tank combines compactness, adjustable high weight and good dynamics of H2 charge/discharge.